2013
DOI: 10.25011/cim.v36i3.19725
|View full text |Cite
|
Sign up to set email alerts
|

Association of pericardial adipose tissue volume with presence and severity of coronary atherosclerosis

Abstract: Association of pericardial adipose tissue volume with presence and severity of coronary atherosclerosis Abstract Purpose: is study was to investigate whether high pericardial adipose tissue (PAT) volume is related to the presence and severity of coronary artery disease (CAD).Methods: Consecutive patients (310 patients) who underwent both dual-source 64-slice CT and percutaneous coronary angiography were recruited into this study. Waist circumference (WC), body mass index (BMI), blood biochemical variables, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The pathological increase in EAT and the concomitance of other metabolic and hemodynamic abnormalities turn it into an adverse lipotoxic, prothrombotic, and proinflammatory organ [ 13 – 15 ]. Our previous study showed that pericardial adipose tissue volume was significantly correlated with traditional cardiovascular risk factors, the severity of CA, and the number of stenotic coronary vessels [ 16 ]. EAT-derived inflammatory cytokines are also significantly related to the plaque vulnerability in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological increase in EAT and the concomitance of other metabolic and hemodynamic abnormalities turn it into an adverse lipotoxic, prothrombotic, and proinflammatory organ [ 13 – 15 ]. Our previous study showed that pericardial adipose tissue volume was significantly correlated with traditional cardiovascular risk factors, the severity of CA, and the number of stenotic coronary vessels [ 16 ]. EAT-derived inflammatory cytokines are also significantly related to the plaque vulnerability in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, recent data have shown that PFV assessed by CT angiography is significantly associated with severe coronary stenosis, plaque burden even in asymptomatic individuals, high-risk plaque features and an increased risk of future cardiac events. [9][10][11] The aim of this study was to investigate the association of PFV with CAD, cardiac risk factors and calcium scoring index in patients with an intermediate pre-test probability of ischaemic heart disease assessed by coronary CT angiography.…”
mentioning
confidence: 99%
“…Studies have shown that EAT is associated with cardiovascular diseases (CVDs) such as arrhythmia, coronary artery disease, and heart failure (Topuz and Dogan 2017 ; Abe et al 2018 ; Mancio et al 2018 ). In addition, there is evidence that the PCAT around the coronary artery is the source of adipocytokines, which influences the development of coronary artery disease (Wang et al 2013 ; Opincariu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%